PENINGKATAN KETERAMPILAN MEMBACA PERMULAAN DENGAN MENGGUNAKAN METODE STRUKTURAL ANALITIK SINTETIK ( SAS ) BAGI SISWAKELAS II SDN 108 / II PERUMNAS - Suci ridhatul safitri; Aprizan; Elvima Nofrianni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study examines the low initial reading skills and abilities of students in second grade at SDN 108/II Perumnas Muara Bungo. This study aims to describe the process and outcomes of second grade students' beginning reading skills using the SAS (Structural Analysis and Synthesis) method.This research method is Classroom Action Research (CLRS). This study consists of two cycles, each consisting of planning, action implementation, observation, and reflection. The subjects of this study were second graders, consisting of one teacher and 22 students at Public Elementary School 108/II Perumnas. The results of this study show that teacher participation in the learning process was 76% in cycle I, meeting I, and increased to 80% in cycle I, meeting II. Furthermore, in cycle II, meeting I and II, the teacher participation increased again to 100%.The results obtained by students during the learning process in Cycle I, meeting I, were 52%, but in Cycle I, meeting II, they increased to 64%, which was considered unachievable. Furthermore, in Cycle II, meeting I, they increased to 88%, and in Cycle II, meeting II, they increased again to 100%, which was considered achieved. Observations of the assessment of students' beginning reading tests in Cycle I showed that only 9 students, or 60%, achieved the target. In Cycle II, 11 students, or 82%, achieved the target and were declared successful.